Culture and Environment as Pillars in the Formation of Sustainable Education - Mónica Sofía Rico Ramírez (Journal of Sustainability Perspectives, 2023)
When we talk about education, those traces of memory that have remained in us come to mind, this is due to complex processes that generate changes in the person and these transformations that impact life and society. You could not talk about education without training. Education is fundamental from the first years and it is essential that it be taught from the family, through which teaching is articulated, knowledge is acquired and consolidated, and virtues for life are formed. One of the biggest challenges in this time of education is to return to comprehensive training, one that leaves individualized teachings and allows learning to be achieved that integrates systems, such as the environment, culture, society and, above all, work. As a team that promotes a more balanced and fairer world, this will be the challenge that makes the difference.